Chaos-based secure data compression (CSDC) - Usama, M. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper focuses the problem of combining compression with encryption for large data. Towards this end, a data encoding scheme for combined data compression and encryption, codenamed CSDC, is introduced. The scheme supports 128-bit key lengths. The data compression is achieved through Huffman coding and encryption through chaotic key-based expansion performed with a Logistic map, a function selected by its high sensitivity to its initial condition, parameter value, ergodicity, random behavior and unstable periodic orbits with long periods. Experimental analysis shows that the compression ratio, security, and performance of CSDC is competitive compared to a selection of prior techniques. Â© 2016 IEEE.